Pengaruh Petuah bobeto Terhadap Kearifan Setempat Kampung Kalaodi, Kota Tidore Kepulauan - Ichsan Sukarno Teng; Agung Murti Nugroho; Susilo Kusdiwanggo (RUAS, 2021)
Indigenous advice are one of the sources of local wisdom somewhere.  Local wisdom becomes an important issue in sustainable environmental control. This research aims to analyze and explain the local wisdom of Kalaodi Village, Tidore Islands City which is influenced by Bobeto indigenous advice.  The research method used is descriptive with the variables of village place, customary rules, collective memory and spatial system. The research procedure includes the stages: describing the topic of information related to advice and object selection; questioning matters related to advice through informants' memories; the decomposition of the information obtained becomes the focus of the problem; data collection and recording field data through observation and interviews; data analysis and writing the results. The results showed Bobeto indigenous advice to be the main factor influencing the local wisdom of Kalaodi Village, Tidore Islands City